Efektivitas Komunikasi Empatik sebagai Strategi Resolusi Konflik Sosial Masyarakat di Kelurahan Sombalabella, Kabupaten Takalar - Henri; nasir (Jurnalika : Jurnal Ilmu Komunikasi, 2026)
Social conflict is a phenomenon that often occurs in people's lives due to differences in interests, values, perceptions, and ineffective communication. If not managed properly, social conflicts have the potential to cause prolonged tensions and disrupt community harmony. This study aims to analyze the effectiveness of empathic communication as a social conflict resolution strategy in Sombalabella Village, Takalar Regency. This study uses a qualitative approach with a descriptive type of research. The data collection technique was carried out through in-depth interviews, observations, and documentation of village officials, community leaders, and residents involved in the process of resolving social conflicts. Data analysis was carried out using the Miles and Huberman interactive model which includes data reduction, data presentation, and conclusion drawn. The results of the study show that empathic communication applied through an attitude of listening, understanding the feelings and viewpoints of the conflicting parties, and open dialogue is able to reduce tension and encourage the achievement of mutual agreement. The effectiveness of empathic communication is supported by the active role of village officials and community leaders as well as a strong deliberation culture, although there are still obstacles in the form of limited communication skills and the emotional condition of the conflicting parties. This research contributes to the development of social communication science by emphasizing the importance of empathic communication as a humanist and participatory approach in the resolution of social conflicts at the local community level.